Fiji's vote for change - Schleich, Anne-Marie (2023)
The recent elections in Fiji resulted in the first democratic transition since 2014 after three opposition parties narrowly voted for a pro–western coalition government with Sitiveni Rabuka as the new prime minister. The election outcome also has geopolitical implications considering the growing US-China confrontation in the Pacific and the renewed US re-engagement in the South Pacific with a focus on Fiji.